Comparison sealing ability in three bioceramic sealers applied in hydraulic condensation technique by using micro-computed tomography - Ping-Hung Lin; Dan-Jae Lin; Heng-Li Huang; Jui-Ting Hsu; Ming-Gene Tu (Elsevier, 2023)
Background/purpose: Sealing ability in root canal obturation has always been a key concern for endodontic success. The purpose of this study was to analyze the percentage of voids in root canal space obturated by using single cone hydraulic condensation with different root canal sealers and to compare those with AH Plus sealer. Materials and methods: Experiments were conducted using twenty 3D-printed upper first premolars. After the buccal root canals were prepared using Ni-Ti rotary instruments, the teeth were divided into four groups: the AH Plus, BC sealer, BC sealer HiFlow, and Endoseal MTA groups. All buccal canals were obturated by single-cone hydraulic condensation. All specimens were scanned using micro-computed tomography and the percentage volume of the voids inside and outside the filled materials (Vin and Vout) at three different canal depth intervals were calculated by a Bruker micro-CT software. Differences according to root canal sealers were evaluated statistically using the Kruskal-Wallis test and the Wilcoxon Rank Sum test at a significance level of 0.05. Results: The results indicated that most of the voids were presented near the interface (Vout), the Vin is very small and not significant different between groups. The Vout decreased in the following order: AH Plus(1.837% ± 1.226%)≅BC sealer (1.225% ± 0.836%)>BC sealer Hiflow(0.349% ± 0.071%)>Endoseal MTA(0.203% ± 0.049%) Conclusion: For the percentage volume of voids between the root canal filling material and root canal surface, though the BC sealer Hiflow is slightly larger than Endoseal MTA, which is still much less than BC sealer and AH Plus.